The Weimar origins of rhetorical inquiry - Marshall, David L. (The University of Chicago Press, 2020)
The Weimar we know and the Weimar we do not know – Idioms of rhetorical inquiry – Heideggerian foundations – Hannah Arendt and the rhetorical constitution of space – Walter Benjamin and the rhetorical construal of indecision – Warburgian image practices – New points of departure in the Weimar afterlife – The possibilities now
Includes bibliographical references and index
Keywords: Benjamin; Walter; Warburg; Aby; Heidegger; Martin; Arendt; Hannah; Heidegger; Martin / 1889-1976; Arendt; Hannah / 1906-1975; Benjamin; Walter / 1892-1940; Warburg; Aby / 1866-1929; Rhetoric / Germany / History / 20th century; Philosophy; German / 20th century; Political science / Germany / Philosophy; Philosophers / Germany; Germany / History / 1918-1933; Germany / Intellectual life / 20th century; Intellectual life; Philosophers; Philosophy; German; Political science / Philosophy; Rhetoric; Germany; 1900-1999; History; Rhetorik; Politische Theorie; Weimarer Republik